PREVALENCE OF ALLERGIC DISEASE AND RELATED ALLERGENS IN PAKISTAN IN 2007 - Ahmad, Farida; Yousaf, Farah; Asif, Shakila (Journal of Postgraduate Medical Institute, 2011)
Objective: To identify the frequency of allergic diseases and the causative factors in patients of all the four Methodology: Secondary data for the year 2007 was analyzed. Skin prick was the method adopted for Results: The results were analyzed and it was found that allergic rhinitis (24.62%) and urticaria (24.04%) were the most common diseases. When city and province data was analyzed it was found that allergic rhinitis was the main allergic disease of Islamabad, NWFP (Khyber Pakhtunkhwa) and Sindh. Similarly urticaria was the commonest allergic disease of Rawalpindi and Baluchistan. Mixed cases of respiratory diseases were common in Punjab and NWFP (Khyber Pakhtunkhwa). Pollen, dust and Paper mulberry were the main aero allergens involved in triggering the disease beside thresher and raw cotton allergens as detected through IgE mediated skin prick test. Conclusion: It is concluded that allergy presents with a wide variety of clinical manifestations. Allergic Rhinitis was the main disease but cases of bronchial asthma and mixed respiratory allergies were also not less. Urticaria was the main skin disease. Aeroallergens were the main causative or triggering factor for respiratory tract allergies and their role was also present in urticaria and eczema cases as compared to food allergens which were playing minimal role. provinces of Pakistan as well as from Rawalpindi and Islamabad.